Wireless Application Converter (WAC) / Hudson Dieh Ung Teck - Hudson , Dieh Ung Teck (2003)
This documentation contains information about the Wireless Application Converter (WAC) for WXES 3181. It is divided into four chapters. These chapters are Chapter 1: Introduction, Chapter 2: Literature Review & Analysis, Chapter 3:Methodology, Chapter 4: System Design, Chapter 5: System Implementation, Chapter 6: System Testing and Chapter 7: System Evaluation. The objective of this documentation is to provide the reader with an overview of the purpose of developing WAC, the architecture and functionality of it. Chapter 1: Introduction provides the introduction for reader about the objectives of developing WA . It covers the objective , development Scopes,targeted user , development limitation and a proposed schedule to finish this project.Chapter 2: Literature Review & Analysis provides information on several terms that are related to this project. These term are taken from the current wireless technology field. Beside, there are two system described in detail that use the similar approach which are the reference for WAC.This Chapter also provides information about the technology quire to develop WAC,which include development software, wireless hardware, protocol for wireless hardware, protocols for wireless network, file storage and server for WAC.Chapter 3: Methodology describes to methodology used to develop WAC.The description include an introduction of method and the reason for using it. Included in this chapter as well, are the requirement of the system. These are the System functionalities, hardware and software requirement. Chapter 4: System Design explains how the system is designed. It cover the system architecture, system modules, system functionality design and module functionality design. Explanation on system architecture covers a brief introduction on the chosen architecture, how this architecture can be implemented in WAC, the advantages for choosing it and the disadvantages. Explanations on other part of this chapter cover the descriptions on the functions involved, the data flowing and how the functions integrating with each others.Chapter 5: System Implementation explains how the system is developed. It covers the coding approach, scripting language and development tool used to develop each module. Chapter 6: System Testing explains the tes ting done on the system. This chapter cover the type of testing being implemented, testing approach and testing resources. It also covers the changes that had been done on the system. Chapter 7: System Evaluation is the final chapter. It covers the problems encountered during the development and the relevant solutions, evaluation by the end user, pros and cons of the system, future enhancement and also knowledge and experience gained from the development. This, chapter will conclude the details about Wireless Application Converter.